2017
DOI: 10.1515/dmpt-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Role of treatment-modifying MTHFR677C>T and 1298A>C polymorphisms in metformin-treated Puerto Rican patients with type-2 diabetes mellitus and peripheral neuropathy

Abstract: Background The study was conducted to investigate potential association between MTHFR genotypes and diabetic peripheral neuropathy (DPN) in Puerto Ricans with type-2 diabetes mellitus (T2DM) treated with metformin. The prevalence of major MTHFR polymorphisms in this cohort was also ascertained. Methods DNAs from 89 metformin-treated patients with T2DM and DPN were genotyped using the PCR-based RFLP assay for MTHFR677C > T and 1298A > C polymorphisms. Frequency distributions of these variants in the study coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…According to early reports, there seems to be a genetic component that may play a role in the development of diabetic peripheral neuropathy (DPN) [37,38]. Jimenez et al found an association between the MTHFR 1298A>C variant and susceptibility to DPN in Puerto Ricans with Type 2 diabetes mellitus treated with metformin [39]. Results suggest that 1298A>C but not 677C>T was associated with DPN susceptibility in this cohort.…”
Section: Clinical Implications Neuropathymentioning
confidence: 75%
See 1 more Smart Citation
“…According to early reports, there seems to be a genetic component that may play a role in the development of diabetic peripheral neuropathy (DPN) [37,38]. Jimenez et al found an association between the MTHFR 1298A>C variant and susceptibility to DPN in Puerto Ricans with Type 2 diabetes mellitus treated with metformin [39]. Results suggest that 1298A>C but not 677C>T was associated with DPN susceptibility in this cohort.…”
Section: Clinical Implications Neuropathymentioning
confidence: 75%
“…Results suggest that 1298A>C but not 677C>T was associated with DPN susceptibility in this cohort. The authors suggested that a differential haplotype structure and LD pattern in the study cohort might explain the observed association of 1298A>C, but not of 677C>T, with DPN susceptibility in these patients [39]. It has also been found by others that individuals with MTHFR 1298A>C, but not 677C>T, have been associated with metabolic syndrome [40].…”
Section: Clinical Implications Neuropathymentioning
confidence: 90%
“…After titles and abstracts screening, 81 nonrelevant records were excluded. The remaining 60 articles and eight additional articles identified from retrieved studies were included in the final meta‐analysis (Al‐Harbi et al, ; Al‐Salihi, Ajeena, Al‐Kashwan, & Al‐Lebban, ; Zidan, El Mougy, Moustafa, El attar, & Mohamed, ; Benrahma et al, ; Bluthner et al, ; Cao, Huang, Mao, & Gao, ; Chang et al, ; Chen, Ning, Zhu, Li, & Shi, ; Chen et al, ; P. Chen, Pan, Sun, Bai, & Fu, ; Dai & Yu, ; El Hajj Chehadeh et al, ; Eroglu et al, ; Errera et al, ; Fekih‐Mrissa et al, ; Fujita et al, ; Guo, Pan, Chu, Guo, & Sun, ; Guo et al, ; Hu, Zhang, Fang, Qin, & Liu, ; Hu, Gan, Li, & Bi, ; Jimenez‐Ramirez et al, ; Ksiazek, Bednarek‐Skublewska, & Buraczynska, ; Lin, Wang, & Liu, ; Liu et al, ; Luo, Yan, Li, Cheng, & Song, ; Luo, Yan, Ma, Cheng, & Song, ; Mao, Gao, Qin, & Shi, ; Mehri et al, ; Mei, Chen, & Zheng, ; Mtiraoui et al, ; Neugebauer, Baba, & Watanabe, ; Nithya et al, ; Odawara & Yamashita, ; Pirozzi et al, ; Qiu, ; Rahimi et al, ; Ramanathan, Harichandana, Kannan, Elumalai, & Sfd, ; Raza, Abbas, Siddiqi, & Mahdi, ; Settin, El‐Baz, Ismaeel, Tolba, & Allah, ; Shang, Wang, & Liu, ; Shi, He, Cheng, Wang, & Liu, ; J. Shi, Li, Yu, Chen, & Tao, ; Shpichinetsky et al, ; Soares et al, ; J. Sun, Xu, Xue, Zhu, & Lu, ; Sun, Xu, & Zhu, ; Sun, Xu, Zhu, & Lu, ; Sun, Xu, Lu, & Zhu, ; Sun, Chen, et al, ; Sun, Wang, Shi, & Yang, ; Wang et al, ; Wang, Hu, Xiao, & Wan, ; Wang, Wang, & Li, ; Wang, Wang, Xue, Chen, & Zou,…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 60 articles and eight additional articles identified from retrieved studies were included in the final meta-analysis (Al-Harbi et al, 2015;Al-Salihi, Ajeena, Al-Kashwan, & Al-Lebban, 2016;Zidan, El Mougy, Moustafa, El attar, & Mohamed, 2019;Benrahma et al, 2012;Bluthner et al, 1999;Cao, Huang, Mao, & Gao, 2005;Chang et al, 2011;Chen, Ning, Zhu, Li, & Shi, 2004;Chen et al, 2010;P. Chen, Pan, Sun, Bai, & Fu, 2008;Dai & Yu, 2012;El Hajj Chehadeh et al, 2016;Eroglu et al, 2007;Errera et al, 2006;Fekih-Mrissa et al, 2017;Fujita et al, 1999;Guo, Pan, Chu, Guo, & Sun, 2005;Guo et al, 2002;Hu, Zhang, Fang, Qin, & Liu, 2009;Hu, Gan, Li, & Bi, 2001;Jimenez-Ramirez et al, 2017;Ksiazek, Bednarek-Skublewska, & Buraczynska, 2004;Lin, Wang, & Liu, 2009;Liu et al, 2014;Luo, Yan, Li, Cheng, & Song, 2007;Luo, Yan, Ma, Cheng, & Song, 2008;Mao, Gao, Qin, & Shi, 2004;Mehri et al, 2010;Mei, Chen, & Zheng, 2012;Mtiraoui et al, 2007;Neugebauer, Baba, & Watanabe, 1998;Nithya et al, 2017;Odawara & Yamashita, 1999;Pirozzi et al, 2018;Qiu, 2009;…”
Section: Study Searchmentioning
confidence: 99%
“…The relationships of MTHFR 677 C>T and ACE I/D polymorphisms with DPN patients presented in this meta-analysis support the view that the MTHFR and ACE genes might play an important role in the development of DPN. Meanwhile, Jiménez-Ramírez, et al carried out a study and sixty-seven percent (67%) of participants carry at least one of these MTHFR polymorphisms [17]. No deviations from Hardy-Weinberg equilibrium were detected.…”
Section: Evidence-based Datamentioning
confidence: 99%